Pengaruh Model Student Teams Achievement Divisions Terintegrasi Crossword Puzzle terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Mirawati, Mirawati (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
Based on the results of initial observations at SMA Negeri 1 Praya Timur, Central Lombok Regency, it was found that students were still less motivated to be active in the learning process, such as lack of student readiness to start lessons, less attention to the teacher while teaching in class, less enthusiastic in learning, and a lack of curiosity when the teacher explains the subject matter. These things are because not all teachers apply appropriate and varied learning strategies, methods and models in learning activities, especially in biology lessons. Learning that takes place in the classroom is still teacher-centered, resulting in students becoming passive because they only tend to listen, pay attention, and take notes on the explanations given by the teacher. This has an impact on students' cognitive learning outcomes. The purpose of this study was to determine "The Effect of the Integrated Crossword Puzzle Student Teams Achievement Divisions Model on Students' Motivation and Cognitive Learning Outcomes" for class XI at SMA Negeri 1 Praya Timur in the 2016/2017 academic year. This type of research is a quasi-experimental research. The population in this study were all students of class XI IPA totaling 91 students. The sampling technique was purposive sampling, in order to obtain research samples, namely class XI IPA 3 as the experimental class, and class XI IPA 2 as the control class. The instruments used in this study were observation sheets of lesson plans implementation, observation sheets of student motivation, and tests of students' cognitive learning outcomes. The data analysis technique used the t-test with the help of SPSS 16 for windows at a significance level of 5%. Based on the results of the research that has been carried out, it is stated that: 1) there is an increase in student motivation by applying the Student Teams Achievement Divisions (STAD) integrated crossword puzzle model with a percentage of the experimental class of 78% and the control class of 75%; and 2) there is an influence of the integrated crossword puzzle Student Teams Achievement Divisions (STAD) model on students' cognitive learning outcomes with a significance value of 0.02 <0.05. Thus it was concluded that the integrated crossword puzzle Student Teams Achievement Divisions (STAD) model had an effect on students' cognitive learning outcomes.